Uncommon sense : shift your thinking : take new action, boost your sales - Harrington, Jill (Jill Elaine) (Figure. 1, 2017)
"You're a talented sales professional, but you face big hairy sales challenges every day and you just can't seem to get anywhere. Why can't I get time with my prospects and clients? Why are my benefit-loaded e-mails and phone calls falling on deaf ears? How do I loosen the stranglehold of an established supplier? How do I convert more leads into sales? How do I stand out when my competition claims the exact same benefits? Same old questions, but in today's market they call for different answers. Uncommon Sense shows you how to shift your thinking and behavior to stand out from the pack and achieve bigger, better sales, faster. It's time to dispense with the common nonsense of dusty old selling imperatives (like, elevator pitches, unique value propositions, and Always Be Closing). Stop thinking like a seller, and start thinking like your customers and prospects. Uncommon Sense shows you how to shift the way you sell ... and the results you get: Provides a toolkit of practical strategies and tactics thatwill improve your access to prospects, enrich engagements with your customers, and transform your results. Features dozens of examples of calls gone seriously wrong, career-changing stories of real salespeople, eye-opening statistics, and tips for thinking your way out of self-defeating behaviors into providing real value for clients. Presents counter-intuitive sales thinking in bite-sized chunks for the busy salesperson who wants practical advice on specific topics. Whether you're a seasoned sales pro or a novice, a sales manager who wants to launch the team to new levels of performance, or a small business owner struggling with the selling role, Uncommon Sense is the personal sales coach you need to shift your thinking, shift your habits, and shift your performance to new heights."--